2020
DOI: 10.1103/physrevmaterials.4.033604
|View full text |Cite
|
Sign up to set email alerts
|

Thermally activated diffusion and lattice relaxation in (Si)GeSn materials

Abstract: Germanium-Tin (GeSn) alloys have emerged as a promising material for future optoelectronics, energy harvesting and nanoelectronics owing to their direct bandgap and compatibility with existing Si-based electronics. Yet, their metastability poses significant challenges calling for indepth investigations of their thermal behavior. With this perspective, this work addresses the interdiffusion processes throughout thermal annealing of pseudomorphic GeSn binary and SiGeSn ternary alloys. In both systems, the initia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
1
12
1
2
Order By: Relevance
“…As we discussed above, this strain relaxation is related to the elongation of pre-existing MDs and not to the generation of new MDs/TDs. The thermal stability of the GeSn BL layer for sample S1 correlates with the high critical temperature of 500 °C for Sn diffusion reported for pseudomorphic GeSn layers . It should be noted that the results in ref may be influenced by a 300 nm thick Ge cap layer.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…As we discussed above, this strain relaxation is related to the elongation of pre-existing MDs and not to the generation of new MDs/TDs. The thermal stability of the GeSn BL layer for sample S1 correlates with the high critical temperature of 500 °C for Sn diffusion reported for pseudomorphic GeSn layers . It should be noted that the results in ref may be influenced by a 300 nm thick Ge cap layer.…”
Section: Discussionsupporting
confidence: 67%
“…The thermal stability of the GeSn BL layer for sample S1 correlates with the high critical temperature of 500 °C for Sn diffusion reported for pseudomorphic GeSn layers. 16 It should be noted that the results in ref 16 may be influenced by a 300 nm thick Ge cap layer. Consequently, the diffusion of Sn in the pseudomorphic layers is characterized by a rather gradual decrease of the Sn content with annealing temperature and time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent annealing experiments realized on GeSn layers, the authors attributed the observed fast and brutal segregation of Sn in relaxed layers to the presence of dislocations, as opposed to diffusional mass transport in pseudomorphic layers. 23,40 The transport of Sn from bulk to surface leads to the formation of self-propelled Sn droplets. The motion of these droplets is likely to be a result of a gradient in the surface Sn content, whereas the directionality of their guided motion can be a consequence of the surface symmetry or atomic steps that are characteristic to the epitaxial growth of strained layers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This efficient defects engineering allows the TL to grow well above its theoretical critical thickness, estimated around 20 nm for a direct growth on the Ge VS. However, when the total thickness of the GeSn stacking increases above 400 nm, the defective area extends, and dislocations propagate toward the surface. , Whereas the diffusion in the bulk is very slow, the nucleation of threading dislocations and their propagation across the TL to reach the surface provide Sn atoms with a much higher mobility and a preferential path to diffuse and segregate on the surface. , It is noteworthy that similar atomistic and microstructural features are also observed when the phase separation is activated by annealing GeSn monocrystalline layers above the growth temperature. In recent annealing experiments realized on GeSn layers, the authors attributed the observed fast and brutal segregation of Sn in relaxed layers to the presence of dislocations, as opposed to diffusional mass transport in pseudomorphic layers. , …”
Section: Resultsmentioning
confidence: 99%